Challenges in secondary prevention after acute myocardial infarction: A call for action. (June 2017) - Piepoli, Massimo F; Corrà, Ugo; Dendale, Paul; Frederix, Ines; Prescott, Eva; Schmid, Jean Paul; Cupples, Margaret; Deaton, Christi; Doherty, Patrick; Giannuzzi, Pantaleo; Graham, Ian; Hansen, Tina Birgitte; et al.
Worldwide, each year more than 7 million people experience myocardial infarction, in which one-year mortality rates are now in the range of 10%, but vary with patient characteristics. The consequences are even more dramatic: among patients who survive, 20% suffer a second cardiovascular event in the first year and approximately 50% of major coronary events occur in those with a previous hospital discharge diagnosis of ischaemic heart disease. The people behind these numbers spur this call for action. Prevention after myocardial infarction is crucial to reduce risk and suffering. Evidence-based interventions include optimal medical treatment with anti-platelets and statins, achieve-ment of blood pressure, lipid and blood glucose targets, and appropriate lifestyle changes. The European Society of Cardiology and its constituent bodies are determined to embrace this challenge by developing a consensus document in which the existing gaps for secondary prevention strategies are reviewed. Effective interventions in relation to the patients, healthcare providers and healthcare systems are proposed and discussed. Finally, innovative strategies in hospital as well as in outpatient and long-term settings are endorsed.